Manipal University Digital Repository: A Study - Pai, Rekha D.; Parmar, Sagender Singh (DESIDOC Journal of Library & Information Technology, 2014)
<!–[if gte mso 9]> <![endif]–> The information and communication technology has given various ways of storing and providing scientific information to the libraries. A digital collection maintained by the university or an academic institution to capture and preserve the intellectual output of its staff and faculty members is called as an institutional repository (IR). The concept of maintaining the IR by academic libraries for the information created by an institution in the form of conference articles, journal articles, audio-video lectures, educational powerpoint presentations, books, patents, etc., is one such way to provide the institutional scientific information openly (with some restriction for the copyrighted articles). The IR has been given a new role to the librarians to be a part of creation of information apart from storing and dissemination of information. Manipal Usniversity (MU) has used EPrints open source software to maintain its IR. This paper describes the elaborative study on Manipal University Digital Repository (MUDR) and its collection growth. Some suggestions that can be implemented to improve the strength and visibility of MUDR are presented, which can be equally applicable to any institutional repository. http://dx.doi.org/10.14429/djlit.34.6119 <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE KN <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:Tunga; mso-bidi-theme-font:minor-bidi; mso-ansi-language:EN-US; mso-fareast-language:EN-US; mso-bidi-language:KN; –> <!–[endif] –>